Method for constructing a dry-wet bimodal self-powered yarn
Patent Information
- Application Number
- CN202510917060.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-03
AI Technical Summary
[0004]尽管现有开发的面料可成功满足人体运动在无汗和有汗场景下的供能需求,但厘米级的二维尺寸限制了其与纺织工艺的兼容性,难以实现多样化呈现,因此需要对以上问题提出一种新的解决方案
[0016]本发明通过SAB与TENG单元的层层堆叠,开发了一种共享电极结构的干湿双模态自供能纱线,这一设计不仅显著提高了能量收集器件的空间利用率,还使其更易于通过多种纺织加工技术集成到各类功能性纺织品中,通过对自供能纱线表面形貌的表征和总体结构的优化,系统评估了纱线的电输出特性、机械性能和洗涤耐久性等,将优化后的自供能纱线以缝纫、编织等方式集成于织物中,开展人体穿戴运动测试,全面评估了器件在实际应用中的可靠性和稳定性。
Smart Images

Figure CN120738816B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of yarn preparation technology, specifically a method for constructing a self-powered yarn capable of being woven in both dry and wet modes. Background Technology
[0002] Soft, breathable fabrics with good skin compatibility offer broad application prospects in areas such as smart fitness tracking, real-time health monitoring, and wearable communication by integrating multiple functional modules. Against this backdrop, one-dimensional electronic devices have attracted widespread attention due to their unique structure-function integration and compatibility with traditional textile processes. Firstly, mature textile manufacturing processes can transform one-dimensional electronic devices into complex multi-dimensional structures. Secondly, compared to traditional planar flexible circuit boards, one-dimensional devices exhibit superior conformability, perfectly conforming to the complex contours of the human body. Finally, the intrinsic multi-level pore structure ensures excellent breathability, while its unique weave topology endows the material with excellent fatigue resistance. These structural advantages not only significantly improve the wearing comfort and lifespan of electronic devices but also provide possibilities for realizing next-generation fabric-based smart wearable systems.
[0003] As the basic unit of fabric, yarn possesses a high degree of freedom in complex weaving structures, enabling seamless integration of sensing, conductivity, and energy transfer functions. Researchers have integrated TENGs, capacitors, and sensors into a single yarn, constructing a multifunctional one-dimensional energy yarn and realizing its sustainable application in various scenarios. In the design of coaxial multilayer yarns, functional layers can be stacked sequentially along the axis, integrating multiple functions while simultaneously constructing a one-dimensional yarn structure. This structure is not only simple to manufacture and easy to scale up, but also significantly saves assembly space, making it a preferred structure for constructing low-cost, multifunctional braidable electronic yarns.
[0004] Although existing fabrics can successfully meet the energy supply needs of human movement in both sweat-free and sweaty scenarios, their centimeter-level two-dimensional size limits their compatibility with textile processes and makes it difficult to achieve diverse presentations. Therefore, a new solution is needed to address these issues. Summary of the Invention
[0005] The purpose of this invention is to provide a method for constructing a self-powered yarn capable of being woven in both dry and wet modes, in order to solve the technical problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for constructing a knittable, dry-wet dual-modal self-powered yarn, comprising at least the following steps:
[0007] First, the cotton fibers are tightly wrapped around the surface of the zinc wire to completely cover its base;
[0008] Subsequently, an SAB unit, namely a yarn-shaped sweat-activated battery unit, was constructed, which includes a zinc wire, a cotton fiber layer, and carbon yarn.
[0009] Next, TENG units, namely fibrous triboelectric nanogenerator units, are constructed on the SAB units;
[0010] The TENG unit includes carbon yarn shared with SAB and silicone fiber as a triboelectric dielectric layer, ensuring that there is a gap between adjacent silicone coils, which is conducive to the penetration of sweat into the cotton fiber layer, thereby ensuring the stable operation of the SAB structure under perspiration conditions.
[0011] This results in a self-powered yarn that can be woven in both dry and wet modes.
[0012] Furthermore, in the SAB structure, the zinc wire is the anode, the cotton fiber layer is the insulating layer, and the carbon yarn is the cathode.
[0013] Furthermore, the zinc wire is covered with a cotton fiber layer on the outside, and the carbon yarn is wrapped around the cotton fiber layer.
[0014] Furthermore, during the construction of the SAB unit and the TENG unit, silicone fiber is used to cover the outside of the yarn-shaped SAB. The winding direction of the silicone fiber is opposite to that of the carbon yarn. The silicone fiber functions as a triboelectric dielectric layer, while the carbon yarn serves as the electrode of the TENG unit. This design, in which two units exist on the same yarn, facilitates the formation of a dry and wet dual-mode self-powered yarn with a shared electrode structure.
[0015] Compared with the prior art, the beneficial effects of the present invention are:
[0016] This invention develops a dry-wet dual-mode self-powered yarn with a shared electrode structure through the layer-by-layer stacking of SAB and TENG units. This design not only significantly improves the space utilization of the energy harvesting device, but also makes it easier to integrate into various functional textiles through various textile processing technologies. By characterizing the surface morphology of the self-powered yarn and optimizing the overall structure, the electrical output characteristics, mechanical properties, and wash durability of the yarn are systematically evaluated. The optimized self-powered yarn is integrated into fabrics by sewing, weaving, and other methods, and wearable motion tests are carried out to comprehensively evaluate the reliability and stability of the device in practical applications. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a schematic diagram illustrating the preparation of the self-powered yarn of the present invention;
[0019] Figure 2 This is a schematic diagram illustrating the preparation and performance analysis of self-powered yarns with different silicone coil gap heights according to the present invention.
[0020] Figure 3 This is a schematic diagram illustrating the preparation and performance analysis of self-powered yarns with different silicone coil gap widths according to the present invention.
[0021] Figure 4 This is a schematic diagram illustrating the working mode and working principle of the TENG unit of the present invention;
[0022] Figure 5 This is a schematic diagram illustrating the electrical performance test and performance output of the TENG unit under dry and wet conditions of the present invention.
[0023] Figure 6 This is a schematic diagram of the durability test of the TENG unit of the present invention;
[0024] Figure 7 This is a schematic diagram illustrating the test results of the SAB liquid absorption saturation volume and output performance of the present invention.
[0025] Figure 8 This is a schematic diagram of the SAB mechanical deformation resistance test of the present invention;
[0026] Figure 9 This is a schematic diagram of the SAB washability test and the self-powered yarn biocompatibility test of the present invention.
[0027] Figure 10 This is a schematic diagram illustrating the self-powered yarn integration method, flexibility, and breathability of the present invention;
[0028] Figure 11 This is a schematic diagram illustrating the output characteristics of the self-powered fabric of the present invention;
[0029] Figure 12 This is a schematic diagram illustrating the dry and wet power supply of sewing fabrics and the charging of the capacitor according to the present invention.
[0030] Figure 13 This is a schematic diagram illustrating the wearable self-powered fabric of the present invention. Detailed Implementation
[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0032] Please see Figure 1(a) Preparation of dry and wet bimodal self-energized yarn using a self-made winding instrument; (b) Characterization of the dry and wet bimodal self-energized yarn (top: SEM and EDS images of the yarn; middle: photographs of the self-energized yarn; bottom: contact angles of carbon fibers before and after hydrophilic treatment); (c) Photographs of the self-energized yarn in knotted, crimped, and bent states; (d) Output voltage of the self-energized yarn in dry state under repeated contact-separation cycles (using pigskin as the contact material); (e) Output voltage of the self-energized yarn after absorbing 5 μL of NaCl solution.
[0033] A method for constructing a knittable, dry-wet dual-modal self-powered yarn includes at least the following steps: Figure 1 As shown in Figure a, researchers fabricated a dry-wet dual-modal self-powered yarn using a self-made winding instrument. First, cotton fibers were tightly wound around the surface of a zinc wire to completely cover its substrate. Then, carbon yarn was wrapped around the zinc wire covering the cotton fibers in a specific structure to construct the SAB structure. In this structure, the zinc wire acts as the anode, the cotton layer as the insulating layer, and the carbon yarn as the cathode. Using a process opposite to the winding direction of the carbon yarn, silicone fibers were wrapped around the yarn-like SAB. In this configuration, the silicone fibers function as a triboelectric layer, while the carbon yarn acts as the electrode of the TENG unit. It is essential to ensure that there are gaps between adjacent silicone coils; this design facilitates the penetration of sweat into the cotton fiber layer, thus ensuring the stable operation of the SAB under human perspiration. Thanks to the precise control of the winding instrument, this dry-wet dual-modal self-powered yarn can be continuously produced at the meter level and can be cut to any desired length for subsequent experimental research.
[0034] Figure 1 Photographs of the prepared yarn, 2.2 mm in diameter, are shown. It consists of a white cotton fiber layer, black carbon yarn, and a transparent silicone fiber coating. The design of the carbon yarn and silicone fiber winding in opposite directions ensures close contact at the intersection, which is crucial for the generation of electrostatic induction effects in TENG. Cross-sectional SEM and EDS images clearly identify the zinc wire structure at the center of the yarn and the outer silicone fiber coating. Surface morphology analysis shows gaps between adjacent silicone coils, with the carbon yarn exposed through these gaps. To enhance the permeability of sweat through these gaps, the carbon yarn was pre-treated electrochemically to alter its surface properties, changing it from hydrophobic to hydrophilic. After treatment, water droplets can be completely absorbed by the carbon yarn within 3 seconds. Furthermore, the yarn can withstand various deformations, including knotting, curling, and bending, while maintaining structural integrity and remaining undamaged. Figure 1 c). The above results indicate that the dry-wet dual-modal self-energized yarn has been successfully constructed according to the design concept, realizing the integration of TENG and SAB units.
[0035] To verify the dual-modal functional characteristics of the devices, the performance of TENG and SAB under dry and wet conditions was tested respectively. For the TENG performance test, the output voltage change of a 5cm long self-powered yarn during periodic contact-separation with pigskin was monitored in real time. Figure 1 d). The self-powered yarn can induce positive and negative voltage pulse signals of approximately 4V during both contact and separation processes. The voltage pulses induced by the contact-separation cycle exhibit a periodic variation, consistent with the AC output characteristics of the TENG. To simulate the sweat penetration process under perspiration conditions, 5μL of NaCl solution was added to the yarn surface ( Figure 1 e). After adding NaCl solution, the yarn voltage rose sharply to 0.22V within seconds and remained stable at approximately 0.33V. The experimental results show that the prepared self-powered yarn can effectively harvest mechanical energy through the TENG unit in a dry state and generate stable electrical energy output through the SAB unit in a wet state.
[0036] Based on the above method for constructing self-powered dry and wet dual-modal yarns, the following analysis and explanation are proposed:
[0037] Optimizing the performance of dry and wet dual-modal self-energized yarns presents a complex challenge, as their overall output characteristics primarily depend on the performance of the two functional units, SAB and TENG.
[0038] As a core component for dry-state energy harvesting, the surface area of the silicone layer in the TENG unit directly affects the device's electrical output performance. With increasing silicone fiber diameter, the effective contact area increases, leading to a significant increase in output voltage and short-circuit current. This is primarily attributed to the enhanced triboelectric effect due to the larger contact area. However, for SAB units, the presence of the surface silicone layer may form a physical barrier, affecting electrolyte diffusion.
[0039] Experiments have shown that the gap height and width of the silicone coil are two key parameters affecting the performance of SAB (Self-Adhesive Block Absorber): an excessively high silicone layer and an excessively small gap can significantly increase the sweat penetration path and liquid penetration resistance, leading to a prolonged response time. Therefore, to achieve efficient energy harvesting in both dry and wet environments, selecting appropriate silicone height and gap size is crucial for balancing the performance of TENG (Temperature Enzyme) and SAB.
[0040] Preparation and performance analysis of self-powered yarns with different silicone coil gap heights
[0041] See Figure 2 (a) Schematic diagram of droplet penetration from the top of the yarn; (b) Droplet penetration from the top of the yarn with different silicone coil gap heights; (c) Discharge curves of yarn with different silicone coil gap heights activated by NaCl solution (current density = 200 μA cm⁻¹).-2 (d) Schematic diagram of droplet penetration from the bottom of the yarn; (e) Water droplet penetration at the bottom of the yarn with different silicone coil gap heights; (f) Response time of the yarn with different silicone coil gap heights to 2 μL NaCl solution; (g) Short-circuit current and (h) output voltage curves of the yarn with different silicone coil gap heights in the dry contact-separation cycle with pigskin; (i) Schematic diagram of silicone coverage on the yarn with different silicone coil gap heights.
[0042] The outermost layer of silicone fibers in the self-powered yarn is designed as a triboelectric layer, with the gaps between adjacent silicone coils serving as sweat penetration channels. When droplets deposit at the gap interface, their permeation kinetics are regulated by three parameters: liquid surface tension, gap boundary wettability, and gap geometry. In this design, the first two parameters are kept constant, while the gap geometry is an adjustable variable. According to the Yang-Laplace equation, the capillary repulsion generated by the inherent hydrophobicity of the silicone fibers hinders liquid penetration into the gaps; this force is inversely proportional to the capillary channel radius. Therefore, under the condition of a constant gap height (H), increasing the gap width (D) can reduce the repulsion force, promote solution penetration, and achieve contact with the SAB unit. The higher the gap wall height, the greater the required gap width needs to be to ensure sufficient contact between the solution and the hydrophilic cotton fiber layer and the carbon yarn layer. Figure 2 a). In this study, sweat permeation behavior and SAB electrochemical performance were systematically investigated by constructing coil gaps of different heights and widths on the yarn surface using silicone fibers of different diameters. Under a fixed gap height, increasing the gap width promoted the transformation of droplets from a non-absorbable state to an absorbable state. For self-energized yarns with gap heights of 0.4 mm, 0.9 mm, and 1.5 mm, NaCl solution permeated from the top of the yarn through the wicking effect at corresponding gap widths of 0.3 mm, 0.8 mm, and 1.0 mm. Figure 2 b). The device was then activated with 50 μL NaCl solution and subjected to an amplitude of 200 μA cm⁻¹. -2 Discharge tests were conducted at current density. The results show that the output voltage and discharge time are quite similar across all tested samples. Figure 2 c).
[0043] To simulate the absorption of sweat on the skin surface, a NaCl solution was dropped onto the leather surface, and the solution was absorbed by the wicking action of the self-powered yarn. Due to gravity, droplets located at the bottom of the device were less likely to penetrate the coil gaps than those at the top of the yarn. Figure 2d). Experimental results show that when the gap height is 0.4 mm and the width exceeds 0.3 mm, the solution can be effectively wicked; however, for self-energized yarns with gap heights of 0.9 mm and 1.5 mm, although increasing the gap width can reduce capillary repulsion, the increased boundary thickness hinders the contact between the droplet and the internal hydrophilic layer. Figure 2 e). This phenomenon was further verified in SAB testing, where yarns with a height of only 0.4 mm and a width of only 0.3 mm were activated by surface-diffused NaCl solution and produced a stable output voltage. Figure 2 f). Given the functional properties of silicone fibers as triboelectric materials in yarns, changes in their thickness and surface winding density may affect TENG performance. Therefore, TENG performance characterization experiments were conducted on yarns with the aforementioned three structural parameters. Figure 2 As shown in g and 2h, all yarns responded to the periodic contact-separation motion with the pigskin, generating output voltage and short-circuit current. Among them, the yarn with a height of 1.5 mm and a width gap of 1.0 mm exhibited the best output voltage and short-circuit current. The area of silicone fiber coverage on the surface of a 5 cm long device was calculated by measuring the yarn diameter (h), the width of a single turn of silicone fiber (a), and the number of silicone turns (N). Figure 2 i) The yarn with a height of 1.5 mm and a width of 1.0 mm has the largest coverage area, approximately 158 mm. 2 The results are in high agreement with the TENG test results. Therefore, it can be inferred that the improved TENG output performance of this structure can be attributed to the increased contact area between the triboelectric material and the skin.
[0044] Preparation and performance analysis of self-powered yarns with different silicone coil gap widths
[0045] See Figure 3 (a) Curves showing the changes in output voltage and short-circuit current with the gap width of the silicone coil; (b) Curve showing the changes in the response time of the yarn to 2 μL NaCl solution with the gap width of the silicone coil; (c) Photographs of the droplet permeation process of yarns prepared with the same silicone coil gap height but different gap widths.
[0046] The above experimental results show that the self-energized yarn with a coil gap height of 0.4 mm can achieve effective wicking of sweat in both directions, and its overall thickness is relatively thin, which is beneficial to traditional textile processing technology. Further adjustments to the coil gap width of this type of yarn can optimize its output performance. As the gap width increases from 0.3 mm to 1.1 mm, the TENG output shows a decreasing trend due to the reduced surface area of the silicone fiber: the output voltage decreases from approximately 5.48±0.40V to 4.48±0.24V, and the short-circuit current decreases from 0.68±0.03μA to 0.4±0.01μA. Figure 3a). The response time of the yarn to NaCl solution droplets was measured simultaneously with different gap widths: when the gap width increased from 0.3 mm to 0.5 mm, the response time significantly shortened, decreasing from 8.0 ± 1.0 s to 4.3 ± 1.2 s; after the gap width exceeded 0.5 mm, the response time tended to stabilize. Figure 3 b). This phenomenon was fully verified by in-situ observation of the NaCl solution permeation process within the yarn. Figure 3 c) When the coil gap width is greater than 0.5 mm, the solution penetration time stabilizes within the range of 4-5 s, matching the response time of the SAB unit. Based on the above data, a coil gap parameter of 0.4 mm height and 0.5 mm width was selected for silicone fiber coating for subsequent experimental research.
[0047] Performance testing of self-powered yarn triboelectric nanogenerator (TENG) unit
[0048] TENG Unit Working Mode and Working Principle
[0049] See Figure 4 (a) Schematic diagram of contact-separation between skin and yarn; (b) Working principle diagram of TENG unit.
[0050] This invention systematically tested the performance of various components of a dry-wet dual-modal self-powered yarn. The system's power supply mechanism consists of two phases: in the initial stage of operation, the TENG unit harvests and supplies energy; when sweat appears and wets the battery, the SAB unit immediately activates and begins supplying energy. In the TENG performance test, this invention uses pigskin to simulate human skin, and a linear motor achieves periodic contact-separation motion between the pigskin and the yarn. Figure 4 a). Figure 4 The diagram illustrates the working principle of a TENG (Triboelectric Engraving) device. Silicone and conductive carbon wire serve as the negative triboelectric material and conductive electrode, respectively, operating according to the principles of a single-electrode TENG. In a static state, no charge transfer is observed due to the lack of contact with the skin. However, when the skin comes into contact with the TENG, charge transfers from the skin to the silicone surface due to the high surface electron affinity of silicone. At this point, the skin surface carries a positive charge, and the silicone surface carries a negative charge; any relative separation generates a potential difference. As the skin moves away from the silicone material, the potential of the TENG electrode drops below the ground potential, driving electrons to flow from the TENG electrode to the ground. Conversely, as the skin moves towards the TENG, the TENG electrode potential rises above the ground potential, driving electrons to flow from the ground to the TENG electrode. This periodic contact-separation motion creates an alternating current between the electrode and the ground, achieving a continuous conversion of mechanical energy into electrical energy.
[0051] TENG Unit Basic Electrical Performance Tests and Performance Output under Dry and Wet Conditions
[0052] See Figure 5 (a) Short-circuit current curves of TENG repeatedly contacting and separating from pigskin with and without NaCl solution; (b) Output voltage curves of TENG repeatedly contacting and separating from pigskin with and without NaCl solution; (c) Short-circuit current curves of TENG repeatedly contacting and separating from pigskin at different frequencies; (d) Output voltage curves of TENG repeatedly contacting and separating from pigskin at different frequencies; (e) Output voltage and power curves as a function of resistance.
[0053] During exercise, the human body's environment undergoes a transition from a dry to a wet state. Using NaCl solution to simulate a sweat environment, the output performance of the TENG was tested under wet conditions. Experimental data showed that when NaCl solution was present on the skin, the short-circuit current of the device significantly decreased from 0.73 μA to 0.17 μA. Figure 5 a) The output voltage also decreased from 4.5V to 1.0V. Figure 5 (b) The performance of the TENG deteriorates significantly under wet conditions. This performance degradation is attributed to the adsorption of water molecules on the silicone rubber surface, which leads to the ionization and neutralization of some electrons, thereby reducing electron transfer and triboelectric effects. Therefore, supplementing the SAB to harvest energy under wet conditions is essential in this process. Notably, when the test frequency increases from 1.3Hz to 3.1Hz, both the short-circuit current and output voltage of the TENG show a significant increasing trend. Figure 5 (c, 5d). This is because, under the same external force, a higher impact frequency can stimulate the flow of external electrons in a shorter time, thereby improving output performance. By changing the external resistance, it can be observed that the output voltage gradually increases with the increase of resistance. When the external resistance reaches approximately 10 MΩ, the instantaneous power reaches its maximum value of 1.85 μW. Figure 5 e).
[0054] TENG Unit Durability Test
[0055] In the field of wearable electronics, durability is one of the key performance indicators determining its practical application value. Especially in applications such as motion monitoring, devices need to withstand multiple challenges including repeated skin friction, mechanical deformation, and sweat corrosion. To comprehensively evaluate the device's durability, 3000 contact-separation cycles were performed at a frequency of 3.1Hz. The short-circuit current remained around 0.77μA, showing no significant attenuation. Figure 6 This fully demonstrates the device's durability and stability. This excellent durability provides crucial assurance for the device's practical applications, particularly offering significant advantages in motion monitoring and health management fields requiring long-term stable operation.
[0056] Self-Powered Yarn Sweat-Induced Battery (SAB) Cell Performance Test
[0057] SAB Liquid Absorption Saturated Volume and Output Performance Test
[0058] like Figure 5 As shown in a and 5b, the output performance of the TENG unit significantly decreases after adsorbing NaCl solution. Therefore, this invention incorporates an SAB unit within the yarn structure to ensure stable power supply even when wet with sweat. This yarn absorbs sweat secreted by the skin, and the liquid rapidly flows within the cotton thread, connecting the inner and outer electrodes of the battery. During this process, a reduction reaction occurs at the positive electrode (O2 + 2H2O + 4e → 4OH-). - At the negative electrode, an oxidation reaction occurs (Zn - 2e → Zn). 2+ This generates a voltage, causing the battery to start working. To further investigate the effect of solution volume on battery output performance, 100 mM NaCl solution was continuously added to the battery device in 10 μL increments using a micropipette, with a cumulative total addition of 70 μL (e.g., ...). Figure 7 (As shown in a). The results showed that after the initial addition of 10 μL of NaCl solution, the battery's output voltage immediately rose from the initial state to 0.45 V, confirming that the electrolyte injection effectively activated the battery. With the increase in the number of electrolyte additions, the output voltage gradually increased, reaching a plateau of 0.55 V when the cumulative addition reached 50 μL. Thereafter, with further increases in electrolyte volume, the output voltage remained relatively stable, indicating that the battery had reached electrolyte saturation. To further determine the battery's electrolyte saturation capacity, the mass change of five identical devices before and after electrolyte absorption was measured, ultimately yielding an electrolyte saturation capacity of 50.20 ± 2.08 μL (…). Figure 7 b).
[0059] Yarn activated by 50 μL of 100 mM NaCl solution at 200 μA cm -2 It can output a stable voltage of 0.65V at the discharge current density. Figure 7 c). The prepared dual-mode self-powered yarn exhibited a discharge time of 1.22 h, which is significantly longer than that of the linear SAB device without an outer silicon fiber coating. This result was also obtained... Figure 7 Supported by the electrolyte evaporation curve in sample c, the surface-coated silicon fibers may extend the discharge duration by suppressing the evaporation of moisture from the internal hydrophilic layer. Furthermore, the power density of this yarn was measured to be 0.82 mA cm⁻¹ using linear sweep voltammetry. -2 ( Figure 7 d), this indicator further confirms the battery's good performance. It is worth noting that under a 2kΩ external load, the maximum output voltages corresponding to the addition of 1, 5, and 10 μL of NaCl solution were 0.13V, 0.39V, and 0.48V, respectively. Figure 7 e), and the electrolyte can be injected at any position on the yarn to achieve repeated activation.
[0060] It can be known Figure 7 (a) Output voltage curve of the yarn activated by repeated additions of 10 μL NaCl solution (load: 2 kΩ); (b) Electrolyte saturation capacity of five yarns after 6 hours of continuous electrolyte supply; (c) Yarns with and without silicone coating at a current density of 200 μA / cm². -2 (d) shows the discharge curves at the time of addition (the inset shows the evaporation curves of the yarn after adding 50 μL of NaCl solution); (e) shows the power density and voltage as a function of current density; (f) shows the output voltage curves of yarns activated by different volumes of NaCl solution (load: 2 kΩ).
[0061] SAB mechanical deformation resistance test
[0062] See Figure 8 (a) Constant current discharge curves of yarn at different bending angles (current density = 200 μA cm⁻¹) -2 ); The constant current discharge curve of a 5cm long yarn after repeated bending (b) and repeated twisting (c) for more than 1000 times (current density = 200μAcm); -2 (d) Constant current discharge curve of a 5cm long yarn repeatedly struck more than 2000 times under a force of 5N (current density = 200μAcm). -2 ).
[0063] As a wearable device designed for practical applications, it will inevitably experience various mechanical deformations and stresses during daily use. To comprehensively evaluate its mechanical stability, a flexible tensile tester was used to conduct bending tests on the yarn battery at different angles (50°, 90°, and 120°). The results showed that the output voltage only experienced minute fluctuations of 0.002V, 0.001V, and 0.001V respectively during the bending process. Figure 8 a) This fully demonstrates the excellent stability of the battery performance under different angular deformation conditions. Furthermore, the yarn underwent over 1000 cycles of bending and torsion testing. Figure 8 b, 8c) The results show that the yarn can still maintain normal working condition after experiencing thousands of mechanical stresses, and its structural integrity and electrochemical performance have not shown significant degradation, which fully demonstrates the excellent mechanical durability of SAB.
[0064] Considering the practical use cases of wearable devices, the devices need to frequently engage in contact-separation cycles with human skin, while also withstanding various mechanical impacts during daily activities. Therefore, impact tests were conducted on the yarn to simulate human slapping motions, in order to evaluate the yarn's output stability under dynamic mechanical stress. Under a constant impact force of 5N (equivalent to normal slapping force), a constant current discharge test (current density of 200μA cm⁻¹) was performed on the yarn. -2 Experimental data shows that although the discharge voltage fluctuated slightly by ±0.02V, the average voltage remained stable at around 0.65V. Figure 8 d). This result not only confirms that SAB has good resistance to mechanical interference, but also provides a strong guarantee for its reliability in practical wearable applications.
[0065] SAB washability test and biocompatibility test of self-powered yarn
[0066] See Figure 9 (a) Performance changes of the yarn during 20 washing cycles; (b) Performance changes at a current density of 200 μA cm⁻¹ -2 Under the conditions, the discharge curve of the yarn before and after 20 machine washes; (c) cell survival rate co-cultured with self-powered yarn.
[0067] To evaluate the yarn's durability in practical use, multiple machine wash tests were conducted, evaluating the performance of various components after 0, 5, 10, 15, and 20 machine wash cycles. The components were placed in a commercial washing machine with detergent, and each wash was set to 10 minutes. After washing, the yarn was rinsed multiple times with deionized water, then air-dried at room temperature. Finally, the performance of each component was tested. Figure 9 As shown in Figure a, after multiple machine wash-dry cycles, the open-circuit voltage of the yarn SAB unit remained above 0.9V without significant fluctuations. Simultaneously, the short-circuit current of the TENG unit also remained stable, indicating that the device was not significantly damaged during repeated washing. A constant current discharge test (current density 200 μA cm⁻¹) was performed on the sample after 20 machine washes. -2 Its discharge duration can still be maintained at over 60 hours. Figure 9 (b) It still retains the ability to power small electrical appliances. To evaluate the biocompatibility of the prepared self-powered yarn, fibroblasts L-929 were co-cultured with SAB and TENG units for 4 days, respectively. The cell viability of the SAB and TENG-treated samples remained close to 100%. Figure 9 c). These data demonstrate that the SAB units within the yarn can be efficiently activated by the electrolyte, and that the self-powered yarn exhibits good biocompatibility, providing a reliable, flexible, and durable power supply solution for textile electronics in a wet state.
[0068] Self-powered yarn integrated into fabric display
[0069] Demonstration of self-powered yarn integration method, flexibility, and breathability.
[0070] See Figure 10 (a) sewing yarn into fabric to create various patterns; (b) weaving yarn to create foldable and crimpable fabrics; (c) the breathability / moisture permeability of energy fabrics woven from self-powered yarns.
[0071] Compared to previously reported dry-wet dual-mode power supply systems, the self-powered yarn developed in this invention employs an innovative one-dimensional structural design (approximately 2.2 mm in diameter), significantly reducing the device size while achieving effective compatibility with various textile processing technologies. Three 22 cm long self-powered yarns are integrated into an elastic fabric substrate using a "serpentine" stitching process. Figure 10 a) This allows the "serpentine" structure of the energy fabric to achieve tensile deformation, which is crucial for body conformation during movement. The self-powered yarn can also be used to create complex patterns, including the letters "SWU" and floral designs, through embroidery. Figure 10 (Illustration a) The yarn within the pattern can be flexibly adapted to the energy requirements of various electronic devices through different series and parallel configurations. Besides being suitable for sewing processes, this device is also compatible with traditional weaving techniques. It uses three sets of three-threaded devices as weft threads and traditional cotton threads as warp threads, woven into an energy-supply fabric using a small loom. Figure 10 b). Thanks to its complete woven structure, this fabric exhibits excellent mechanical flexibility and good softness, allowing it to closely conform to the skin. This woven structure endows the energy fabric with excellent flexibility, easily achieving complex deformations such as folding and curling. Figure 10 (b. Illustration). The results show that even after these complex deformation operations, the fabric can still maintain its structural integrity without any deformation, fully demonstrating its adaptability to complex mechanical deformation.
[0072] In addition, the air permeability and moisture permeability of the woven fabric were also tested. Figure 10 c) By continuously blowing air into the fabric with a bulb syringe, the paper strip at the back of the fabric can be blown up; by placing the fabric above a beaker containing hot water and then inverting another beaker on top of the fabric, the writing on the upper beaker becomes blurred after 4 minutes, indicating that water vapor can penetrate the fabric. This energy fabric exhibits excellent breathability and moisture permeability, a characteristic that significantly improves its comfort as a power source in wearable applications.
[0073] Demonstration of self-powered fabric output characteristics
[0074] See Figure 11(a) Energy fabrics that power LEDs using TENG (dry) and SAB (wet) modes respectively; (b) Output voltages of TENG and SAB units in the energy fabric in the dry state; (c) Output voltages of TENG and SAB units in the energy fabric in the wet state.
[0075] Figure 11 The demonstration showed the working state of the woven fabric in both dry and wet states. Without skin contact, the LED could not be lit on the dry fabric. When the dry fabric was repeatedly tapped, the LED turned on and off accordingly. After adding NaCl solution to the fabric, the SAB was successfully activated and the LED could be lit continuously. To further verify the working state of the self-supplied fabric in both dry and wet environments, a large external resistor was connected, and NaCl solution was used to simulate sweat to test the fabric's performance in both dry and wet states. When the fabric surface was not covered with electrolyte solution and was in a static state, the SAB had almost no output voltage, while when the fabric was tapped by hand, the TENG could generate an output voltage of approximately 10V. Figure 11 b). After spraying the electrolyte solution onto the fabric surface and allowing it to stand for a few minutes, the output voltage of SAB is approximately 2.7V. Figure 11 c) When the fabric is dry, the TENG unit can supply power normally; however, when the fabric is patted by hand, the TENG unit has almost no output and cannot support the normal operation of electrical appliances. These research results confirm that the TENG unit mainly undertakes the power supply task of the system in the dry state, while the SAB unit becomes the dominant power supply component in the wet state.
[0076] See Figure 12 (a) Demonstration of dry and wet power supply using sewing fabric; (b) Charging a capacitor using energy fabric in TENG mode; (c) Charging a 10μF capacitor using energy fabric in TENG (dry) and SAB (wet) modes.
[0077] The LED is powered by fabric sewn into a small floral pattern. When the LED is tapped, it receives alternating current, causing it to alternate between bright and dim light. After adding NaCl solution to activate the battery, the LED can emit light stably for a long time. Figure 12 a). An energy fabric with an integrated "SWU" pattern successfully demonstrated dual-mode charging of capacitors of various sizes. In a dry state, through continuous hand-tapping, the fabric could charge 1.0, 3.3, and 10.0 μF capacitors; the larger the capacitor value, the longer it took to achieve a significant voltage increase. Figure 12(b) To highlight the dual-mode power supply characteristics under dry and wet conditions, the study further demonstrated the continuous charging process of a 10μF capacitor under dry-wet conditions. In the first 35 seconds in the dry state, it was charged to 0.4V via the TENG unit, and the voltage remained stable for 30 seconds after the tapping stopped. Spraying NaCl solution onto the fabric surface activated the SAB unit, allowing it to continue supplying power to the capacitor. Once the fabric surface was wetted, the capacitor voltage rapidly increased to 2.7V within 120 seconds, fully demonstrating the fabric's dual power supply capability under both dry and wet conditions. Figure 12 c). These results strongly validate that yarn-integrated fabrics, as a dual-modal power supply system, can provide sufficient power to microelectronic devices in both dry and wet conditions, and also provide strong support for their practical application in wearable devices.
[0078] Wearable self-powered fabric demonstration
[0079] To verify the feasibility of this fabric in real-world applications, the invention sews the device under the armpit of a shirt and connects it to an LED via a wire, using it as a warning light during physical exercise. Considering the need for contact-separation or friction between the skin and the fabric, the device is ultimately sewn into the area from the armpit to the waist of the shirt. Figure 13 To create optimal friction conditions, a healthy male volunteer wore this energy T-shirt and, in an environment with 75% humidity and a temperature of 28°C, traveled at a speed of 4.0 km / h. -1 The volunteers ran at a speed on a treadmill. During the run, periodic contact and separation occurred between their palms and the fabric, and the friction between the silicone and their skin caused the LEDs to alternate between bright and dark. After about 10 minutes, the sweat secreted by the volunteers' bodies wet most of the yarn, and the LEDs switched to a continuous lighting state. This experiment effectively simulated the operation of the dual-modal self-powered fabric in a real-world application scenario. The energy triggered by skin contact and human perspiration successfully powered a small electronic device, thus fully verifying the feasibility and reliability of self-powered yarn in practical applications.
[0080] In summary:
[0081] This invention constructs a dual-modal power supply device based on a coaxial yarn structure, utilizing the layered stacking of TENG and SAB units, achieving continuous power supply under both sweaty and dry conditions during human exercise. The device, from the inside out, consists of zinc wire, cotton fiber, carbon yarn, and silicone fiber, with the carbon yarn serving as both the cathode of the SAB unit and the back electrode of the TENG. Using a laboratory-built electronic yarn winding machine, this dual-modal power supply yarn can be continuously produced on a meter-scale basis. By adjusting the height of the outermost silicone fiber and the distance between each turn of silicone, the performance of the SAB and TENG can be balanced, allowing for efficient operation in both dry and wet conditions. The yarn exhibits excellent wash resistance and resistance to mechanical deformation; its performance remains largely unchanged after thousands of bending / twisting cycles and multiple machine washes. Through traditional weaving and sewing techniques, the yarn can be integrated into fabrics for diverse applications, greatly expanding its application scenarios and design possibilities. To further verify the practical application effect of the dual-modal power supply yarn, this invention underwent wear experiments in a running scenario. The results show that the system can continuously drive the LEDs regardless of whether there is no sweat or sweat secretion, fully demonstrating its enormous application potential in the field of smart clothing and wearable devices. This invention not only provides new ideas for the development of bimodal systems, but also offers a novel solution to the self-powering problem of wearable devices.
[0082] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A method for constructing a self-powered yarn capable of both dry and wet weaving, characterized in that: At least the following steps are included: First, the cotton fibers are tightly wrapped around the surface of the zinc wire to completely cover its base; Subsequently, an SAB unit, namely a yarn-shaped sweat-activated battery unit, was constructed. The SAB unit includes a zinc wire, a cotton fiber layer, and carbon yarn, with the carbon yarn wrapped around the cotton fiber layer. Next, a TENG unit, namely a fibrous triboelectric nanogenerator unit, is constructed on the SAB unit. Silicone fibers are wrapped around the yarn-like SAB, and the winding direction of the silicone fibers is opposite to that of the carbon yarn. The TENG unit includes carbon yarn shared with SAB and silicone fiber as a triboelectric dielectric layer, ensuring that there is a gap between adjacent silicone coils, which is conducive to the penetration of sweat into the cotton fiber layer, thereby ensuring the stable operation of the SAB structure under perspiration conditions. This results in a self-powered yarn that can be woven in both dry and wet modes.
2. The method for constructing a self-powered yarn capable of both dry and wet weaving according to claim 1, characterized in that: In the SAB structure, the zinc wire is the anode, the cotton fiber layer is the isolation layer, and the carbon yarn is the cathode.
3. The method for constructing a self-powered yarn capable of being woven in both dry and wet modes according to claim 2, characterized in that: The zinc wire is covered with a layer of cotton fibers on the outside.
4. The method for constructing a self-powered yarn capable of both dry and wet weaving according to claim 3, characterized in that: During the construction of the SAB unit and TENG unit, the silicone fiber functions as a triboelectric layer, while the carbon yarn serves as the electrode of the TENG unit. This design, in which two units coexist on the same yarn, facilitates the formation of a dry and wet dual-mode self-powered yarn with a shared electrode structure.
Citation Information
Patent Citations
Multifunctional power generation greenhouse cloth and preparation method thereof
CN111758462A
Friction nanometer power generation composite yarn and preparation method and application thereof
CN115323552A